Representation of Game Phrase-Making Mechanisms in Educational Dictionary: Practical Lexicography - E. I Rogaleva; L. S. Golovina; I. M. Mikhailova (Научный диалог, 2021)
The practical experience of the vocabulary representation of the mechanisms of game phraseology is described, the difficulties of lexicography of phraseological units built on the game paradox are listed, the ways to solve the problem of etymologization of phraseological games in the educational dictionary are showed. The main positions of the innovative technology for constructing educational phraseological dictionaries in paper format are presented. The relevance of the research is due to the great developmental impact of phraseological games on the addressee-child and the need to improve the system of their lexicographic description for educational purposes. The novelty of the research lies in the appeal to the unexplored problematic of describing phraseological games and the development of a technique for etymological paraphrasing, including interpretive and plot-compositional techniques, which are implemented in a twolevel configurative structure of etymological paraphrase. Special attention is paid to lexicographic techniques that allow revealing the specifics of phraseological games built on false imagery, as well as phraseological games, the content plan of which is not opposed to the expression plan, and their actual meaning is logically justified and motivated. Examples of dictionary entries of new phraseographic projects of the Experimental Laboratory of Educational Lexicography of Pskov University are given — a quest dictionary and a phraseological puzzle dictionary, the genres of which adequately reveal the specifics of phraseological games.